Core Curriculum in Headaches for Neurologists: Proposal from the Portuguese Headache Society - Parreira, Elsa (2025)
Continuous education in headaches is a priority for the Portuguese Headache Society. We present a proposal for a Core Curriculum in Headaches for Neurologists and Neurology-trainees, developed based on the ‘Headache Core Curriculum’ of the International Headache Society (IHS), revised in May 2020. This document is not merely a translation of the original but rather a structured adaptation to the national context, incorporating differences in the organization and structure of the content. Thus, this article presents the national proposal for the Core Curriculum in Headaches, while the annex includes the Portuguese translation of the original IHS document into Portuguese, which is also available on the IHS page (https://ihs-headache.org/en/learning-centre/ihs-core-curriculum/). In addition to the contents of each topic, the annex includes a list of recommended articles.